Income taxation by residence and/or source in Lesotho - Hlajoane, Dorothy Masebili (Department of Commercial Law, 2023)
"The Income Tax Acts themselves impose a territorial limit; either that from which the taxable income is derived must be situate in the United Kingdom or the person whose income is to be taxed must be resident there", per Lord Herschell in Colquhoun v Brooks (1889) 2 TC 490 at 498 These remarks by Lord Herschell even though directed at the United Kingdom tax system in 1889 seem to capture the situation in the new tax law in Lesotho. A recurring question for any tax system to date is is taxation by either residence and/or source appropriate? This question inspired my research into the examination of the new Lesotho Income Tax Order No 9 of 1993.